Determining the comprehensibility and acceptability of phonological varieties of Filipino-English as used in academic lectures - Sarile, Angela Feredo (1986)
This study conducted in an attempt to determine the comprehensibility and acceptability of phonological varieties of Filipino-English as used in academic lectures. The study concludes that the phonological and prosodic features of selected Filipino-English varieties generate certain evaluative reactions toward such varieties.
Thesis (Ph.D. Language Teaching)--University of the Philippines, Diliman.
Keywords: University of the Philippines (Diliman). -- College of Education -- Graduate students; University of the Philippines (Pampanga) -- Graduate students; University of the Philippines (Pampanga) -- American students; English language -- Phonology; English language -- Study and teaching (Higher) -- Philippines; Filipino language -- Study and teaching (Higher) -- Philippines; English language -- Study and teaching (Higher) -- Ilocano speakers; English language -- Study and teaching (Higher) -- Cebuano speakers; English language -- Study and teaching (Higher) -- Hiligaynon speakers; English language -- Usage; Filipino language -- Usage; Native language and education -- Philippines; Language and education -- Philippines; Reading comprehension